The Quality of Competence Through Nursing Career Paths Among Indonesian Nurses in Hospital Settings - Hadi, Muhammad; Rahmawati, Dina; Heny Purwati, Nyimas; Natashia, Dhea; Slametiningsih, Slametiningsih; Hasanah, Idyatul (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
ntroduction: Nurses play a pivotal role in the provision of healthcare services both within the Indonesian context and on a worldwide scale. The development of nursing competence is crucial in order to guarantee the provision of high-quality healthcare services. To examine the elements that are linked to the enhancement of nurse competence by means of the adoption of nursing career paths within hospital settings in Indonesia. Methods: A descriptive analytical design, utilising a cross-sectional approach with a sample size of 197 nurses. The data was obtained by administering a meticulously evaluated questionnaire, designed by the researchers, to the participants. The questionnaire's validity (r=0.361) and reliability (r=0.933) were thoroughly assessed. The analysis of the research data was conducted utilising multiple linear regression tests. Results: As established through the use of multiple linear regression tests, demonstrate a statistically significant positive association (p<0.05) between organisational loyalty, organisational support, guidance, and financing, and the implementation of nurse competence quality. The obtained coefficient of determination was 0.260, suggesting that the four independent variables considered in this study have the ability to collectively account for 26% of the variability observed in the implementation of nurse competence quality. It is important to note that the remaining variation is likely impacted by additional factors not included in the analysis. The guiding element has been identified as the primary determinant in the cultivation of quality competence within hospital settings while implementing nursing career routes. Conclusion: The present study establishes that factors such as organisational loyalty, organisational support, mentorship for nurses, and financial resources for career advancement have a significant impact on the enhancement of nursing competency along the career trajectory within hospital settings. The variable exerting the most significant influence is the provision of instructions for nurses.